In vivo study of Centella asiatica leaf extract cream for Matrix Metalloproteinase-1 inhibition and collagen enhancement to prevent photoaging - Sri Purmawanti; Joko Wahyu W; Titiek Sumarawati (Medisains)
Background: Ultraviolet B (UVB) exposure accelerates skin aging, causing wrinkles and increasing matrix metalloproteinase-1 (MMP-1) activity, which degrades collagen. Centella asiatica (CA) has well-documented anti-inflammatory and antioxidant properties that may counteract UVB-induced photoaging. However, studies on its topical formulation for MMP-1 inhibition and collagen enhancement remain limited.